The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10592-011-0273-2
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and landscape genetics in the endangered subterranean rodent Ctenomys porteousi

Abstract: In order to devise adequate conservation and management strategies for endangered species, it is important to incorporate a reliable understanding of its spatial population structure, detecting the existence of demographic partitions throughout its geographical range and characterizing the distribution of its genetic diversity. Moreover, in species that occupy fragmented habitats it is essential to know how landscape characteristics may affect the genetic connectivity among populations. In this study we use ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 96 publications
2
35
1
2
Order By: Relevance
“…In general, population genetic studies focusing on a solitary species with low vagility, such as the Baird's pocket gopher, are rare (e.g., Hambuch and Lacey 2000, Connior and Risch 2010, Lopes and De Freitas 2012, Mapelli et al 2012). This study found that both mitochondrial and microsatellite data were informative in understanding population processes across a series of localities of G. breviceps in the Brazos Valley of eastern Texas.…”
Section: Discussionmentioning
confidence: 99%
“…In general, population genetic studies focusing on a solitary species with low vagility, such as the Baird's pocket gopher, are rare (e.g., Hambuch and Lacey 2000, Connior and Risch 2010, Lopes and De Freitas 2012, Mapelli et al 2012). This study found that both mitochondrial and microsatellite data were informative in understanding population processes across a series of localities of G. breviceps in the Brazos Valley of eastern Texas.…”
Section: Discussionmentioning
confidence: 99%
“…Five loci (Ds1, Ds3, Ds19, Ds46, and DS98) deviated significantly from HWE after Bonferroni correction, while there was no evidence of LD (Bonferroni corrected p < 0.05); these same loci showed evidence of null alleles but not stuttering errors were detected. Because D. merriami's social structure encompasses groups of individuals with different degrees of relatedness (see relatedness results below), some evidence of deviation from HWE or null alleles is expected (i.e., not resulting from a systematic nonamplification of alleles; Bergl & Vigilant, 2007; Mapelli, Mora, Mirol, & Kittlein, 2012). Hence, all eight loci were included in the following analyses.…”
Section: Population Geneticsmentioning
confidence: 99%
“…Studies involving rodents in America have been conducted mainly in areas with anthropogenic impact, including urban areas (Gardner-Santana et al 2009;Chambers and Garant 2010;Mapelli et al 2012;Munshi-South 2012;Marrotte et al 2014;Anderson et al 2015;Chiappero et al 2016;Combs et al 2018). On the other hand, we found only two works that were conducted with rodents in desert environments, specifically kangaroo rats in the Chihuahuan desert.…”
Section: Resultsmentioning
confidence: 99%
“…An aspect worth mentioning is the development of additional methods to assess connectivity in terms of the relationship between effective and genetic distances, like the generalized linear models, which prevailed in studies with rodents (Kittlein and Gaggiotti 2008;Mapelli et al 2012;Marrotte et al 2014;Cosentino et al 2015). We should also highlight the use of species distribution models for the construction of connectivity hypotheses in landscape genetics, as these combine presence data (localities where the species has been recorded) and climate data associated with that locality, also considering vegetation cover, topography, and other environmental variables (Rolland et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation